Quality circle time in the primary school : a handbook of good practice - Mosley, Jenny; Tew, Marilyn (Milton Park, Abingdon, Oxon : Routledge, Taylor & Francis Group, 2014)
"Jenny Mosley's Quality Circle Time model involves establishing an on-going, timetabled process of circle-meetings for adults and children. As a basis for teaching relationship skills, enhancing self-esteem and building a positive behaviour management and anti-bullying policy, circle time should not only increase confidence and "emotional intelligence" in pupils, but should also contribute towards a positive whole-school ethos. This classic text provides a rationale, framework and whole-school model for Quality Circle Time specifically for secondary schools and further education colleges"--
Includes bibliographical references (pages 184-186) and index.
Keywords: High school teaching -- Handbooks, manuals, etc; Education, Secondary -- Activity programs -- Handbooks, manuals, etc; EDUCATION / General